What Do Science, Technology, and Innovation Mean from Africa? - Mavhunga, Clapperton (The MIT Press, 2017)
Clapperton Mavhunga's collection of essays about science, technology, and innovation (STI) from an African perspective opens with the idea, "Things do not (always) mean the same from everywhere; when we insist that only 'our' meaning is the meaning, we silence other people's meanings." Mavhunga and his contributors argue that our contemporary definitions of STI are those of countries and cultures that have acquired their dominance of others through global empires, and as a counter to that, Mavhunga seeks to put the concepts of STI into question, exploring what the technological, scientific, and innovative might mean from Africa in lieu of outside introductions or influences. We strongly feel that this book is suited to the Knowledge Unlatched program because of the difficulty of reaching markets and readers in Africa with print books. We feel unlatching would go a long way toward helping Mavhunga reach an important audience for this work that we have been previously unable to reach.